Integrating the Mararang Postpartum Tradition into Biomedical Care: An Interdisciplinary Study of Health Beliefs, Communication, and Maternal–Infant Outcomes - Putra Apriadi Siregar; Aulia Rahma Ritonga; Rani Suraya; Muhammad Rezebri; Prima Yanti Siregar; Mhd. Iqbal; Sabila Pratiwi; Apriliani Apriliani; Desty Adinda (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
ntroduction: Traditional postpartum care practices remain an integral aspect of maternal and child health in indigenous communities. Mararang tradition is a postpartum care tradition that continues to be widely practiced among Batak postpartum mothers, as it is believed to accelerate maternal and infant recovery through heat therapy. . This study aims to examine the historical evolution of the mararang tradition, its cultural significance, and its implications for maternal and infant health. Methods: A qualitative phenomenological approach was employed to explore the experiences of postpartum mothers practicing the mararang tradition. Data were collected through in-depth interviews with postpartum mothers, their husbands, traditional leaders, and healthcare providers in North Sumatra Province. Source triangulation, methodological triangulation, and data analysis were applied in this research. Thematic and content analyses were conducted to explore key dimensions of health beliefs, communication, and the transformation of the mararang tradition over time. Results: Participants ascribed thermal balance, comfort, and social support to mararang, while acknowledging potential risks from heat and smoke. Communication between families and midwives produced adaptive forms (e.g., moderated heat, improved ventilation, time?limited sessions), balancing cultural continuity with safety. We synthesise a conceptual model showing how explanatory beliefs, family authority, and professional guidance co?produce negotiated care. Conclusion: Mararang persists through culturally safe adaptations facilitated by respectful dialogue; practical safeguards (distance from heat source, ventilation, exclusion post?caesarean) can be embedded within routine postpartum care. Programmes should integrate culturally anchored counselling and risk?mitigation protocols, enabling context?sensitive maternal and newborn care.